Service discovery in a dynamic office environment / Ooi Soo Teck - Ooi , Soo Teck (2007)

(untitled)
The raising of pervasive computing environments of heterogeneous network has provided a major impact to replicate the network-based service discovery technologies in ad hoc networks and mobile networks. The ability to interact and control network devices with different modalities within the home and office environment could be very beneficial to many users. The Service discovery in computers and handheld devices enabled them to interact with one another through heterogeneous wired and wireless networks. These services advertise their existence in a dynamic way and the devices may automatically discover them together with their properties. Service discoveries were used in home and office environment where the devices in homes and offices can be monitored and controlled over the Internet by handheld devices such as laptop and mobile devices. These devices which are based on different technologies are able to communicate and be discovered over the internet with the service discovery technologies. However, there are few issues that prevent these to be realized due to the complexities of the ad hoc environment. This thesis focuses and provides a preliminary study and analysis of the service discovery technologies in an ad hoc network along with the requirements that need to be met. The challenges are to communicate devices of different communication protocols in a heterogeneous network and platform and the devices are able to be accessed over wide-area network which currently are poor in support. An architecture of devices interaction is proposed based on the analysis of requirements. A new service discovery concept for dynamic office network is developed and presented in a scenario where a salesman, bringing his pocket pc into his client office which was enabled with UPnP support, able to discover a printer around and print his product details without any network setup and configuration. The service-oriented OSGi (Open Service Gateway Initiative) framework is proposed as the base platform of the architecture. A prototype is partially deployed on the knopflerfish OSGi framework to evaluate the possibility of the proposed architecture. This prototype demonstrates and satisfies the requirement that services could be discovered over different networks and communication platform such as UPnP and OSGi.